Human to Mosquito Transmission of Dengue Viruses - Carrington, Lauren B.; Simmons, Cameron P. (Frontiers in Immunology, 2014)
The successful transmission of dengue virus from a human host to a mosquito vector requires a complex set of factors to align. It is becoming increasingly important to improve our understanding of the parameters that shape the human to mosquito component of the transmission cycle so that vaccines and therapeutic anti-virals can be fully evaluated and epidemiological models refined. Here we describe these factors, and discuss the biological and environmental impacts and demographic changes that are influencing these dynamics. Specifically, we examine features of the human infection required for the mosquito to acquire the virus via natural blood feeding, as well as the biological and environmental factors that influence a mosquito’s susceptibility to infection, up to the point that they are capable of transmitting the virus to a new host.